Fabricating an Alibi as a Form of Obstruction of Justice in Homicide: An Analysis of the 2024 Palembang Junior High School Student Case - Yolanda, Aldina; Saptian, Aril; Aldiansyah; Muhtarom, Satrio; Rohim, A. (Journal of Literacy and Education, 2026)
This study aims to analyze fabricated alibis as a form of obstruction of justice in homicide cases through the case study of the murder of a junior high school student in Palembang in 2024. This research employs a normative legal method using statutory, conceptual, and case approaches. Data were collected through library research involving legislation, legal literature, and relevant scholarly works. The findings indicate that a fabricated alibi constitutes the provision of false information intended to conceal facts and hinder the law enforcement process. From the perspective of Indonesian criminal law, such conduct can be classified as obstruction of justice because it interferes with investigations, prosecutions, and court proceedings. The murder case of the junior high school student in Palembang demonstrates that efforts to conceal evidence through fabricated alibis can obstruct the search for material truth. Therefore, firm law enforcement against both homicide perpetrators and individuals involved in obstructing judicial processes is necessary to ensure justice and legal certainty.